A highly efficient sulfadiazine selection system for the generation of transgenic plants and algae. Issue 3 (13th September 2018) - Tabatabaei, Iman; Dal Bosco, Cristina; Bednarska, Marta; Ruf, Stephanie; Meurer, Jörg; Bock, Ralph
Summary: The genetic transformation of plant cells is critically dependent on the availability of efficient selectable marker gene. Sulfonamides are herbicides that, by inhibiting the folic acid biosynthetic pathway, suppress the growth of untransformed cells. Sulfonamide resistance genes that were previously developed as selectable markers for plant transformation were based on the assumption that, in plants, the folic acid biosynthetic pathway resides in the chloroplast compartment. Consequently, the Sul resistance protein, a herbicide‐insensitive dihydropteroate synthase, was targeted to the chloroplast. Although these vectors produce transgenic plants, the transformation efficiencies are low compared to other markers. Here, we show that this inefficiency is due to the erroneous assumption that the folic acid pathway is located in chloroplasts. When the RbcS transit peptide was replaced by a transit peptide for protein import into mitochondria, the compartment where folic acid biosynthesis takes place in yeast, much higher resistance to sulfonamide and much higher transformation efficiencies are obtained, suggesting that current sul vectors are likely to function due to low‐level mistargeting of the resistance protein to mitochondria. We constructed a series of optimized transformation vectors and demonstrate that they produce transgenic events at very high frequency in both the seed plant tobacco and the green alga Chlamydomonas reinhardtii . Co‐transformation experiments in tobacco revealed that sul is even superior to nptII, the currently most efficient selectable marker gene, and thus provides an attractive marker for the high‐throughput genetic transformation of plants and algae.